Nifedipine maintenance tocolysis and perinatal outcome: an individual participant data meta‐analysis. (23rd August 2016) - van Vliet, EOG; Dijkema, GH; Schuit, E; Heida, KY; Roos, C; van der Post, JAM; Parry, EC; McCowan, L; Lyell, DJ; El‐Sayed, YY; Carr, DB; Clark, AL; et al.
Abstract : Background: Preterm birth is the leading cause of neonatal mortality and morbidity in developed countries. Whether continued tocolysis after 48 hours of rescue tocolysis improves neonatal outcome is unproven. Objectives: To evaluate the effectiveness of maintenance tocolytic therapy with oral nifedipine on the reduction of adverse neonatal outcomes and the prolongation of pregnancy by performing an individual patient data meta‐analysis (IPDMA). Search strategy: We searched PubMed, Embase, and Cochrane databases for randomised controlled trials of maintenance tocolysis therapy with nifedipine in preterm labour. Selection criteria: We selected trials including pregnant women between 24 and 36 6/7 weeks of gestation (gestational age, GA) with imminent preterm labour who had not delivered after 48 hours of initial tocolysis, and compared maintenance nifedipine tocolysis with placebo/no treatment. Data collection and analysis: The primary outcome was perinatal mortality. Secondary outcome measures were intraventricular haemorrhage (IVH), necrotising enterocolitis (NEC), infant respiratory distress syndrome (IRDS), prolongation of pregnancy, GA at delivery, birthweight, neonatal intensive care unit admission, and number of days on ventilation support. Pre‐specified subgroup analyses were performed. Main results: Six randomised controlled trials were included in this IPDMA, encompassing data from 787 patients ( n = 390 for nifedipine; n = 397 for placebo/no treatment). There was no difference between the groups for the incidence of perinatal death (risk ratio, RR 1.36; 95% confidence interval, 95% CI 0.35–5.33), intraventricular haemorrhage (IVH) ≥ grade II (RR 0.65; 95% CI 0.16–2.67), necrotising enterocolitis (NEC) (RR 1.15; 95% CI 0.50–2.65), infant respiratory distress syndrome (IRDS) (RR 0.98; 95% CI 0.51–1.85), and prolongation of pregnancy (hazard ratio, HR 0.74; 95% CI 0.55–1.01). Conclusion: Maintenance tocolysis is not associated with improved perinatal outcome and is therefore not recommended for routine practice. Tweetable abstract: Nifedipine maintenance tocolysis is not associated with improved perinatal outcome or pregnancy prolongation. Tweetable abstract: Nifedipine maintenance tocolysis is not associated with improved perinatal outcome or pregnancy prolongation.